Ecocriticsm as the Development of Teaching Materials in Literary Theories and Appreciation Courses - saifulloh, ahmad iklil (International Journal of English Education and Linguistics (IJoEEL), 2021)
Eco Criticism or known as Literary Ecology which was popularized by Greg Gerrad has become a rare scientific discourse if it synergizes with the Indonesian character of education which is one of the educational pillars of the ministry of education. The resonance of these two scientific clumps between environment and literature to be the main topic promoted to realize the value of character education no 16 which is concerned about environment. To achieve this goal, this research using research and development by Plomp in order to form a form of book materials of Eco criticism as applied literary in education. The results obtained in the application of the ecological characteristics of literature which include the main elements, namely Pollution, Position, Pastoral, Wilderness, Apocalypse, Dwelling, Animal, Future the earth in a form of field test for students are 87.42 and expert validation 92.3%, media 95, 3%, and 92.3% language in the course of literary theory and appreciation of English language education, the Faculty of Teacher Training and Education, Majapahit Islamic University of Mojokerto.